Fatores de influência dinâmica processual da Prefeitura Municipal de Vitória - Scherrer, Rodrigo (2008)
The following essay has a purpose to identify the factors that affects the dinamic of the administrative processes at the Prefeitura Municipal de Vitória (municipal government of Vitoria). It’s throughout the administrative processes that citizens, compan